Adsorption of Anion Dye from Aqueous Solution by Activated Carbon Coated Monolith in a Batch System - Darmadi, Darmadi; Thaib, Anwar (Jurnal Rekayasa Kimia & Lingkungan, 2010)
The adsorption of an anion dye, methyl orange, from aqueous solutions on polymer based carbon coated monolith was studied in a batch system. The kinetics of adsorption with respect to the initial dye concentration was investigated. Langmuir and Freundlich isotherms were applied to describe the experimental data. Equilibrium data fitted well to the Freundlich model for concentration range (0 160 mg/L). The maximum adsorption capacity of the carbon with BET surface area of 431 m2/g obtained from the Freundlich model was 36.72 (mg/g) (L/mg)1/n. The pseudo-first-order and pseudo-second-order kinetic models were employed to describe the kinetic data. The experimental data fitted well to the pseudo-second-order kinetic model with constant rates 5.42x10-4 and 2.22x10-4 g/(min-mg) for initial concentrations 50 and 100 mg/L, respectively. Keywords: adsorption, anion dye, carbon coated monolith